First Language Egocentricism and Learning English: Finding the Balance (Journal of Management and Social Sciences, 2022)
Students face the English language shock in an attempt to learn it. This is due to first language egocentrism. First language egocentrism makes it difficult for foreign students to find balance between first language and English. Previous studies have provided solutions to this problem but not having access to an aggregate of these solutions seems to be a problem confronting foreign students. This paper, therefore, aggregates the solutions for the benefits of the students. The paper uses secondary data, adopts qualitative research method and random, purposive and convenience sampling techniques. Among the available studies on this topic available to the researcher, the most relevant ones are selected and reviewed. The finding reveals that the aggregate of the solutions is cosmopolitan outlook which can be achieved through these adjustment strategies: utilization of school resources, participation in dormitory and campus activities, language support, campus counseling service, students’ organisations, pre-acculturation, social identification and intercultural adaptation, bilingual programme, motivation, favourable educational context, errors and feedback.  Keywords    First language egocentricism, cosmopolitan outlook, adjustment strategies